Decision-making autonomy of women and other factors of anemia among married women in Ethiopia: a multilevel analysis of a countrywide survey - Fentanesh Nibret Tiruneh; Degnet Teferi Asres; Mesfin Wogayehu Tenagashaw; Hirut Assaye (BMC, 2021)
Abstract Background Anemia is one of the world's public health problem, especially in developing nations. The majority of women of childbearing age (15-49) are affected by anemia. Women's role in the decision-making process is significant for their health and related issues such as anemia. So far, there is no evidence of women's decision-making autonomy on anemia. Consequently, this study aimed to robustly examine both individual- and group-level women's decision-making autonomy and other determinants of anemia among married women in Ethiopia. Methods We examined data from an Ethiopian demographic and health survey conducted in 2016. Our analysis included 9220 married women of childbearing age (15-49 years). For bivariate analysis, we applied the chi-squared (X2) test. The relationship between individual and group-level women's decision-making autonomy and anemia was assessed using multilevel binary logistic regression models while adjusting other socio-demographic and economic characteristics. Results In this study the magnitude of anemia was 30.5% (95% CI; 29.5-31.4). According to our multilevel analysis, group-level women's autonomy was found to be negatively related with anemia than individual-level women's autonomy (AOR = 0.53, 95% CI = 0.41-0.69). In addition, the indicator of women's wealth index at group level was a protective factor (AOR = 0.68, 95% CI =0.51-0.90) to develop anemia. Among individual-level indicators women's age (AOR = 0.73, 95% CI = 0.60-0.89), use of contraceptive (AOR = 0.66, 95% CI = 0.55-0.81), BMI (AOR = 0.71, 95% CI = 0.59-0.86) and employment status (AOR = 0.88, 95% CI = 0.79-0.98) were negatively related with anemia. While women who follow Muslim religion (AOR = 1.62, 95% CI = 1.32-1.97,), women who had five and above number of children (AOR = 93, 95% CI = 1.53-2.46), and who were pregnant (AOR = 1.21, 95% CI = 1.04-1.40) were positively associated with anemia. Our final model showed that around 27% of the variability of having anemia was because of group-level differences (ICC = 0.27, P < 0.001). In addition, both individual and group-level factors account for 56.4% of the variance in the in the severity of anemia across communities (PCV = 56.4%). Conclusions Our study showed that empowering women within households is not only an important mechanism to reduce anemia among married women but also serves as a way to improve the lives of other women within the society.